Assessing the sustainability of pension reforms in Europe - Grech, Aaron George (London, 2010)
"Spurred by the ageing transition, many governments have made wide-ranging reforms, dramatically changing Europe’s pensions landscape. Nevertheless there remain concerns about future costs, while unease about adequacy is growing. This study develops a comprehensive framework to assess pension system sustainability. It captures the effects of reforms on the ability of systems to alleviate poverty and maintain living standards, while setting out how reforms change future costs and relative entitlements for different generations. This framework differs from others, which just look at generosity at the point of retirement, as it uses pension wealth - the value of all transfers during retirement. This captures the impact of both longevity and changes in the value of pensions during retirement. Moreover, rather than focusing only on average earners with full careers, this framework examines individuals at different wage levels, taking account of actual labour market participation. The countries analysed cover 70% of the EU’s population and include examples of all system types. Our estimates indicate that while reforms have decreased generosity significantly, in most, but not all, countries the poverty alleviation function remains strong, particularly where minimum pensions have improved. However, moves to link benefits to contributions have made some systems less progressive, raising adequacy concerns for women and those on low incomes. The consumption smoothing function of state pensions has declined noticeably, suggesting the need for longer working lives or additional private saving for individuals to maintain pre-reform living standards. Despite the reforms, the size of entitlements of future generations should remain similar to that of current generations, in most cases, as the effect of lower annual benefits should be offset by longer retirement. Though reforms have helped address the financial challenge faced by pension systems, in many countries pressures remain strong and further reforms are likely."